2017
DOI: 10.1007/s00059-017-4589-7
|View full text |Cite
|
Sign up to set email alerts
|

Interatrial septum versus right atrial appendage pacing for prevention of atrial fibrillation

Abstract: IAS pacing is safe and as well tolerated as RAA pacing. Although IAS pacing may fail to prevent permanent AF occurrence and recurrences of AF, it is able to not only improve interatrial conduction, but also reduce AF burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…However, studies showed conflicting results and the most optimal position is yet not solidly defined. 9 A pacing location at which the intra-atrial conduction delay is minimized may be most beneficial for the patient. In this study, we demonstrated that the reduction of TAT and cCDCB at BB is particularly achieved by LRA pacing, especially in patients with pre-existing conduction disorders at BB during SR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies showed conflicting results and the most optimal position is yet not solidly defined. 9 A pacing location at which the intra-atrial conduction delay is minimized may be most beneficial for the patient. In this study, we demonstrated that the reduction of TAT and cCDCB at BB is particularly achieved by LRA pacing, especially in patients with pre-existing conduction disorders at BB during SR.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that pacing from the high atrial septum reduces the risk of AF, 2 , 5–8 but a large multi-centre study failed to show the benefit of atrial septal pacing. 9 It has been postulated that a pacing site with the smallest inter-atrial conduction delay reduces AF initiation and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Although HASp is believed to improve interatrial conduction and reduce AF burden, HASp alone has failed to show consistent benefits 4,5 . One reason may be that the area of the HAS is difficult to implant using conventional tools.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that right atrial appendage pacing (RAAp) exacerbates interatrial conduction delay (IACD), whereas high atrial septal pacing (HASp) may decrease AF incidence and duration 1–3 . However, other studies have shown that right atrial septal pacing alone did not suppress AF 4,5 . Previous methods of atrial lead implantation have used tined or screw leads.…”
Section: Introductionmentioning
confidence: 99%
“…97 Zhang et al agreed that LAS pacing can reduce AF burden, and proved the safety of septal pacing. 98 Multisite atrial pacing mainly refers to biatrial pacing and RA bi-site pacing, and its electrophysiological mechanisms for the prevention of AF include the following: improving atrial depolarization and/or repolarization and ameliorating anisotropic conduction in the atrium, shortening the intra-atrial conduction time and restoring the synchronization of electrical activity in both atria, and shortening the atrial refractory period and reducing the dispersion of the atrial refractory period. 99,100 For patients with intra-atrial block, i.e., the P-wave time in the ECG >120 ms, the benefit of multisite atrial pacing is more obvious.…”
Section: Changing the Pacing Sitementioning
confidence: 99%